INCREASING THE LITERACY OF THE CREATIVE ECONOMY AND MSMES IN THE DIGITAL ERA AT SMA NEGERI 3 TONDANO - Gaby Dainty Julliet Roring; Riedel Brey; Trezeraldo Tumelap; Leydi Tenda; Revalina Sangeroki (JF Publisher, 2024)
The digital era has brought major changes to various aspects of life, including the economy, so that creative economy literacy has become an important skill for the younger generation. MSMEs, as the backbone of the economy, have a strategic role in creating jobs and economic development. However, students' understanding of the creative economy and MSMEs is still limited, so formal education needs to provide more effective teaching. This research aims to improve students' creative economy literacy through a learning seminar held at SMA Negeri 3 Tondano. Using a qualitative approach with descriptive design, this seminar involved 4 main topics: introduction to the creative economy, the role of MSMEs, adaptation of the younger generation to the Society 5.0 Era, and opportunities and challenges in starting a business. Data were collected through observation and interactive discussions. The results of the study show that this seminar has succeeded in increasing students' understanding of the creative economy and MSMEs, as well as encouraging their motivation to be entrepreneurial. Students also show the ability to develop creative business ideas based on local potential and the use of technology. In conclusion, this seminar makes a positive contribution in equipping students with relevant economic literacy for the digital era, and can be used as a learning model in other schools.